A review of the new MBIE Report on the Marsden Fund - Chambers, Geoff (New Zealand Science Review, 2017)
​The New Zealand Ministry of Business, Innovation and Employ-ment (MBIE) has recently completed a report on the way that the Marsden Fund works (MBIE 2017). In many ways this is an excellent document. It describes the history and purpose of the fund and explains how it operates. It also compares Marsden to other granting agencies overseas (Section 3). The authors consulted widely with stakeholders, identified many issues in their findings (Section 4) and made a set of recommendations (Section 5). Although a lot of key points were revealed, the MBIE team seems to have been consistently just wide of the mark, in the estimation of this reviewer. In this short article I identify those key topics that have been a source of long-term concern for many applicants and commentators. It is hoped that these, together with the original MBIE report, may stimulate wider discussion in the scientific community.